Research guide for gender-disaggregated analysis of climate change impacts and adaptation - Bryan, Elizabeth; Kovarik, Chiara; Passarelli, Simone; Sproule, Katie (International Food Policy Research Institute, 2015)
This toolkit provides a compilation of tools developed for and used in the research project titled “Enhancing Women’s Assets to Manage Risk under Climate Change: Potential for Group-Based Approaches,” (2011-2014) which was supported by the Federal Min-istry for Economic Cooperation and Development, Germany, and was undertaken as part of the CGIAR Research Program on Policies, Insti-tutions, and Markets (PIM). Section 1 provides an introduction to the research project and answers frequently asked questions regard-ing research on gender, climate change, assets and collective action. Section 2 provides a brief description of the various qualitative and quantitative tools used in the project with links to relevant briefs and papers that use those tools. This toolkit highlights the tools and techniques that were used in the aforesaid research project and is therefore not meant to be an exhaustive list of information and tools related to gender, climate change, and collective action. It is aimed, primarily, at researchers interested in the topic of gender and climate change; however, the studies summarized here also provide insights for practitioners implementing gender and climate change projects. Section 3 provides links to other external resources, including other tools and initiatives we think are useful to practitioners and research-ers doing work related to gender and climate change.